Money in monetary policy design under uncertainty: The two-pillar Phillips curve versus ECB-style cross-checking - Günter W. Beck; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
The European Central Bank has assigned a special role to money in its two pillar strategy and has received much criticism for this decision. In this paper, we explore possible justifications. The case against including money in the central bank's interest rate rule is based on a standard model of the monetary transmission process that underlies many contributions to research on monetary policy in the last two decades. Of course, if one allows for a direct effect of money on output or inflation as in the empirical 'two-pillar' Phillips curves estimated in some recent contributions, it would be optimal to include a measure of (long-run) money growth in the rule. In this paper, we develop a justification for including money in the interest rate rule by allowing for imperfect knowledge regarding unobservables such as potential output and equilibrium interest rates. We formulate a novel characterization of ECB-style monetary cross-checking and show that it can generate substantial stabilization benefits in the event of persistent policy misperceptions regarding potential output. Such misperceptions cause a bias in policy setting. We find that cross-checking and changing interest rates in response to sustained deviations of long-run money growth helps the central bank to overcome this bias. Our argument in favor of ECB-style cross-checking does not require direct effects of money on output or inflation.
urn:nbn:de:hebis:30-43980
Keywords: E32; E41; E43; E52; E58; 330; Monetary Policy; Quantity Theory; Phillips Curve; European Central Bank; Policy Under Uncertainty; Geldpolitik; Entscheidung bei Unsicherheit; Quantitätstheorie; Phillips-Kurve; Zentralbank; EU-Staaten